Effect of an empowerment-based nutrition promotion program on food consumption and serum lipid levels in hyperlipidemic Thai elderly - Boonyasopun U. (2014)
This quasi-experimental study examined the effects of an empowerment-based nutrition promotion program on food consumption and serum lipid levels among hyperlipidemic Thai elderly. Fifty-six experimental subjects received the program; 48 control subjects maintained their habitual lifestyle. The statistical methods used were the t-test, Z-test, and χ2/Fisher's exact test. After the program, the consumption of high saturated fat, cholesterol, and simple sugar diets was significantly lower for the experimental group than for the control group. The percentage change of the serum total cholesterol of the experimental subjects was significantly higher than that of the control subjects. The number of experimental subjects that changed from hyperlipidemia to normolipidemia significantly increased compared to that for the control subjects. The implementation of this program was related to an improvement in food consumption and serum lipid levels among hyperlipidemic Thai elderly and, therefore, has implications for practice. © 2008 The Authors Journal compilation © 2008 Blackwell Publishing Asia Pty Ltd.